2008
DOI: 10.2178/jsl/1230396925
|View full text |Cite
|
Sign up to set email alerts
|

A model for a very good scale and a bad scale

Abstract: Given a supercompact cardinal κ and a regular cardinal λ < κ, we describe a type of forcing such that in the generic extension the cofinality of κ is λ, there is a very good scale at κ, a bad scale at κ, and SCH at κ fails. When creating our model we have great freedom in assigning the value of 2κ, and so we can make SCH hold or fail arbitrarily badly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 6 publications
3
30
0
Order By: Relevance
“…The proof of this claim adapts an argument due to Solovay, Reinhardt, and Kanamori [7]. For details, see Lemma 2 in [6]. Now, define the chain as follows.…”
Section: The Constructionmentioning
confidence: 83%
See 2 more Smart Citations
“…The proof of this claim adapts an argument due to Solovay, Reinhardt, and Kanamori [7]. For details, see Lemma 2 in [6]. Now, define the chain as follows.…”
Section: The Constructionmentioning
confidence: 83%
“…In 2008 Gitik-Sharon [2] showed two important consistency results about scales: that failure of SCH does not imply weak square, and the existence of a very good scale does not imply weak square. The result was generalized by Sinapova [6] for singular cardinals of arbitrary cofinality. The Gitik-Sharon model provided much of the motivation behind the construction in Neeman [5].…”
Section: Theoremmentioning
confidence: 95%
See 1 more Smart Citation
“…In her doctoral thesis Dima Sinapova answered this question. Sinapova [27] introduced a version of the Gitik-Sharon forcing which makes a supercompact cardinal κ into a singular cardinal of uncountable cofinality, and showed that in her model there are cofinal sets carrying a non-good scale and a very good scale. (2) Itay Neeman [23] used a variant of the Gitik-Sharon construction to produce a model in which the Singular Cardinals Hypothesis fails at a singular cardinal κ of cofinality ω, and κ + has the tree property.…”
Section: Proof We Work In the Modelmentioning
confidence: 99%
“…The proof adapts easily to produce other failures 2 κ = λ > κ + , but one has to increase the large cardinal assumption to δ supercompactness for δ > (ν + ) V . The work of Gitik-Sharon and Cummings-Foreman was generalized by Sinapova [26] to produce an extension with arbitrary cofinality for κ. It is likely, but not known, that similar generalizations are possible with our construction.…”
mentioning
confidence: 99%